2020
DOI: 10.1371/journal.pone.0241080
|View full text |Cite
|
Sign up to set email alerts
|

Liposome/gold hybrid nanoparticle encoded with CoQ10 (LGNP-CoQ10) suppressed rheumatoid arthritis via STAT3/Th17 targeting

Abstract: Coenzyme Q10 (CoQ10), also known as ubiquinone, is a fat-soluble antioxidant. Although CoQ10 has not been approved as medication by the Food and Drug Administration, it is widely used in dietary supplements. Some studies have shown that CoQ10 has anti-inflammatory effects on various autoimmune disorders. In this study, we investigated the anti-inflammatory effects of liposome/gold hybrid nanoparticles encoded with CoQ10 (LGNP-CoQ10). Both CoQ10 and LGNP-CoQ10 were administered orally to mice with collagen-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Jhun et al [146] used a liposome and gold hybrid nanoparticle to encapsulate CoQ10 (LGNP-CoQ10) for curbing Th17 activity in the CIA mouse model [146]. These CoQ10 NPs were administered orally, and the authors found a greater reduction in arthritic score, and a reduction in Th17 numbers and cytokine levels, compared to unencapsulated CoQ10 [146]. Regulatory T cells are remarkable mediators of tolerance through production of IL-10 and their ability to competitively inhibit DC-mediated co-stimulatory activation of T cells [28,126].…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jhun et al [146] used a liposome and gold hybrid nanoparticle to encapsulate CoQ10 (LGNP-CoQ10) for curbing Th17 activity in the CIA mouse model [146]. These CoQ10 NPs were administered orally, and the authors found a greater reduction in arthritic score, and a reduction in Th17 numbers and cytokine levels, compared to unencapsulated CoQ10 [146]. Regulatory T cells are remarkable mediators of tolerance through production of IL-10 and their ability to competitively inhibit DC-mediated co-stimulatory activation of T cells [28,126].…”
Section: T Cellsmentioning
confidence: 99%
“…The antioxidant coenzyme Q10 (CoQ10) inhibits the transcription factor STAT3, a critical regulator for Th17 effector function [144,145]. Jhun et al [146] used a liposome and gold hybrid nanoparticle to encapsulate CoQ10 (LGNP-CoQ10) for curbing Th17 activity in the CIA mouse model [146]. These CoQ10 NPs were administered orally, and the authors found a greater reduction in arthritic score, and a reduction in Th17 numbers and cytokine levels, compared to unencapsulated CoQ10 [146].…”
Section: T Cellsmentioning
confidence: 99%
“…utilized liposome/gold hybrid NPs to deliver Coenzyme Q10 (CoQ10) in a CIA mouse model. [ 85 ] Histological staining results indicated that the NPs loaded with CoQ10 significantly reduced Th17 cell populations and IL‐17 expression. IL‐23 is an important pro‐inflammatory cytokine that promotes the production of Th17 cells.…”
Section: Therapeutic Targeting Strategymentioning
confidence: 99%
“…The immunomodulatory effects of CoQ 10 have also been shown in other mouse models of RA like collagen-induced arthritis (CIA). In a very recent study, the oral administration of CoQ 10 encoded in liposome/gold hybrid nanoparticles (LGNP CoQ 10 ) for 10 weeks showed the reduction of the pathology scores of RA including bone damage, cartilage damage and immune cells infiltration [ 144 ]. The levels of pro-inflammatory cytokines such as IL6, TNF, IL17 and IL1 were reduced in the joints of CoQ 10 -treated mice.…”
Section: Coq 10 As a Potential Therapeutic Tool In Systemic Autoimmune Diseasesmentioning
confidence: 99%